Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury After SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2025)
Subarachnoid hemorrhage (SAH) is a type of stroke with a high disability and mortality rate. Apoptosis caused by massive damage to mitochondria in neuron cells and inflammatory responses caused by high extracellular ATP lead to poor outcomes. USP30 is a deubiquitinating enzyme that inhibits mitophagy, resulting in a failure to remove damaged mitochondria in a timely manner after SAH; nevertheless, the pathway through which USP30 inhibits mitophagy is unknown. This study evaluated the neuroprotective role and possible molecular basis by which inhibiting USP30 to attenuate SAH-induced EBI by promoting neuronal mitophagy. We used an in vitro model of hemoglobin exposure and an in vivo model of intravascular perforation. Increased expression of USP30 was found after SAH in vivo and in vitro, and USP30 inhibition expression in SAH mice treated with MF094 resulted in significant improvement of neurological injury and inflammatory response and mediated good outcomes, suggesting a neuroprotective effect of USP30 inhibition. In cultured neurons, inhibition of USP30 promoted ubiquitination modification of mitochondrial fusion protein 2 (MFN2) by E3 ubiquitin ligase (Parkin), separating damaged mitochondria from the healthy mitochondrial network and prompting mitophagy, causing early clearance of damaged intracellular mitochondria, and reducing the onset of apoptosis. The high extracellular ATP environment was meliorated, reversing the conversion of microglia to a pro-inflammatory phenotype and reducing inflammatory injury. USP30 inhibition had no autophagy-promoting effect on structurally and functionally sound mitochondria and did not inhibit normal intracellular ATP production. The findings suggest that USP30 inhibition has a neuroprotective effect after SAH by promoting early mitophagy after SAH to clear damaged mitochondria.